Spreadsheets to expedite taxonomic publications by automatic generation of morphological descriptions and specimen lists - Magalhaes, Ivan L. F. (Zootaxa, 2019)
It is now generally accepted that we are going through a major mass extinction event that is causing biodiversity loss at alarming rates (Barnosky et al. 2011). We also know that many species remain to be formally described (e.g. Huber 2014), and concerns have been raised as to whether we will be able to document these before they go extinct (Costello et al. 2013). On one hand, the number of recognized species increases exponentially (e.g. Agnarsson et al. 2013; Sangster & Luksenburg 2015). On the other, taxonomic descriptions are becoming more complete and detailed, which is necessarily more time-consuming, leading to an overall decline in the number of species described per taxonomist (Sangster & Luksenburg 2015). In this scenario, any method or protocol that increases efficiency in taxonomic descriptions is welcome.